2005
DOI: 10.1159/000086435
|View full text |Cite
|
Sign up to set email alerts
|

Sun Protection in Renal Transplant Recipients: Urgent Need for Education

Abstract: Background: Renal transplant recipients (RTR) are considered as a high-risk group of skin cancer development. Objective: The aim of the present studywas to find out the knowledge about the harmfulness of sunlight and the methods of sun protection among RTR. Material and Methods: 151 RTR (91 males and 60 females) were surveyed using a specially designed questionnaire. Results: The knowledge about the danger of sunlight exposure among RTR appeared to be very unsatisfactory. Only 40.4% of patients knew that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 37 publications
4
33
0
5
Order By: Relevance
“…Previous studies have described sun protection measures in OTRs in countries with lower levels of solar ultraviolet radiation than subtropical Australia, including the USA, Canada, Northern Europe and Iran [5,6,7,8,13,14,15]. While their categorization of sun protection measures varied, the frequency of ever- versus never-use of a particular measure was lower than in Queensland OTRs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have described sun protection measures in OTRs in countries with lower levels of solar ultraviolet radiation than subtropical Australia, including the USA, Canada, Northern Europe and Iran [5,6,7,8,13,14,15]. While their categorization of sun protection measures varied, the frequency of ever- versus never-use of a particular measure was lower than in Queensland OTRs.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of these sun protection measures has been studied extensively in the general Australian population [4] but similar information has not been presented for higher-risk OTRs. In North America and Europe, studies of organ transplant patients suggest that, in general, their use of sun protection measures is suboptimal [5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Substantial knowledge gaps were previously reported in studies on Italian melanoma patients [21], on persons at higher risk for developing melanoma in the UK [22] and also on transplant recipients [23]. A survey on awareness and knowledge about NMSC conducted on the general population in 7 countries [5] showed that 42% of Italians rarely or never applied a sunscreen when outside, with only Spain (47%) and the USA (49%) reporting a more frequent lack of sunscreen use.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that continuous education for 6 months is effective in increasing our patients' compliance to sunscreen use as well as in encouraging them for self skin examination. 1 However, the education needs to be emphasized repeatedly as some attitudes are strong and hard to change [3,4] .…”
Section: Correspondence and Opinionsmentioning
confidence: 99%